Explicitation in Malay to English translation of Usman Awangs sahabatku (kepada Dr M K Rajakumar) - Mansour Amini (Tanjong Malim, 2021)
Explicitation in Malay to English translation of Usman Awangs sahabatku (kepada Dr M K Rajakumar) by Mansour Amini